PENGARUH PENGARUH PENGOLESAN TOOTH MOUSSE TERHADAP pH SALIVA PENDERITA HIPERTENSI DI PUSKESMAS BANJARBARU SELATAN KOTA BANJARBARU - hilda fauji; Naning Kisworo Utami; Meggy Wulandari Kai; Ida Rahmawati (JURNAL TERAPIS GIGI DAN MULUT, 2026)
MINISTRY OF HEALTH OF THE REPUBLIC OF INDONESIA BANJARMASIN HEALTH POLYTECHNIC DENTAL THERAPY STUDY PROGRAM APPLIED UNDERGRADUEATE PROGRAM DENTAL HEALTH YEAR 2025 ABSTRACT Undergraduate Thesis HILDA FAUJI The Effect Of Tooth Mousse Smearing On The pH Saliva Of Hypertensive Patients At The Banjarbaru Health Center South Of Banjarbaru City Mentor (1) drg. Naning Kisworo Utami., M.Kes, Mentor (2) Meggy Wulandari Kai, S. Tr.Kep, M.Tr.Kep xiv + 64 pages; 14 table; 9 pictures; 16 attachment Indonesians are still facing serious dental and oral health problems. According to data from the Indonesian Dental Association (PTGI) in 2022, around 70% of Indonesian people experience tooth decay. Research published in the International Journal of Clinical Dentistry and Wellness highlights that hypertensive patients who take antihypertensive drugs experience various oral health problems, such as dry mouth, taste changes, halitosis, bleeding gums, and mucosal lesions. This side effect can worsen the oral health condition of hypertensive patients. This study aims to determine the effect of tooth mousse application on salivary pH in hypertensive patients at Banjarbaru Selatan Community Health Center, Banjarbaru City. This research used a quasi-experimental method with a one-group pretest and posttest design. The sample was selected using purposive sampling technique, with a total of 33 participants. Data were analyzed using the Paired Sample T-Test statistical test. The results showed that the mean salivary pH before the application of tooth mousse was 5.912 and increased to 6.539 after the application. The result of the Paired Sample T-Test showed a p-value of 0.000 < α = 0.05, indicating that the null hypothesis was rejected and the alternative hypothesis was accepted. In conclusion, tooth mousse application had a significant effect on salivary pH in hypertensive patients at Banjarbaru Selatan Community Health Center. It is recommended that health professionals, especially in the field of oral health, conduct promotive and preventive efforts such as educating the public on the use of tooth mousse to maintain salivary pH balance and prevent dental caries, particularly in high-risk groups such as hypertensive patients. Keywords References : Tooth Mousse; Salivary pH; Hypertension : 39 (2012 - 2024)